Security Issues in Cloud Computing and Existing Solutions- a Survey - Revathi, M; Priya, R (International Journal of Engineering and Technology, 2018)
Cloud computing is turning into an outstanding fluff word these days. It is an appealing innovation for long-haul benefits through cost diminishment and change in business results. It additionally tackles numerous issues of stereotyped processing, including taking care of more volume of burdens, introducing programming updates, and, utilizing overabundance figuring cycles. Regardless, the contemporary advancement has new troubles, for instance, data security, information inborn, and trans-code data storing. Cloud computing is consumed and compared to the modern transformation. Cloud administrations are conveyed from server farms, for example, Amazon, Google, Microsoft et cetera, all through the world. The quick blast in the territory of "Cloud computing" moreover expands outrageous wellbeing concerns. This paper review cloud structure and the monstrous evaluation of Cloud computing with the essential consideration on holes and security issues. We perceive the best security dangers and their present arrangements.Â
Keywords: Cloud computing; security challenges; denial of service; sniffer attack; CAPTCHA breaking; data leakage.